Journalistic investigations and cabinet crises in the Third Polish Republic (selected examples) - Adamczyk, Wojciech (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2018)
This article focuses on the influence of investigative journalism on the system of government, and, in particular, on the functioning and break-up of cabinet coalitions in Poland after 1989. It focuses on the parliamentary-cabinet form of government. The source of conflicts which led to the loss of the necessary trust or accelerated the fall of the government were often crises caused by the work of investigative journalists, in which they disclosed facts uncomfortable for members of the Council of Ministers, related to them either directly, through their own reprehensible activities, or indirectly, through the activities of their closest associates. The aim of this article is to show that the unmasking of scandals involving members of the government, their associates or politicians and officials from their political base is a catalyst that can generate cabinet crises, including the collapse of the government. Analyses show the impact of scandals revealed during the term of office of four governments, that of Waldemar Pawlak, Leszek Miller, Jarosław Kaczyński and Donald Tusk.

Przedmiotem rozważań jest wpływ dziennikarstwa śledczego na system rządów, a w szczególności na funkcjonowanie i rozpad koalicji gabinetowych w Polsce po 1989 roku. Cezura ta ma bezpośredni związek z ukształtowaniem się w ramach transformacji systemowej parlamentarno-gabinetowej formy sprawowania rządów. Źródłem konfliktów prowadzących do utraty niezbędnego zaufania lub przyspieszających upadek rządu były niejednokrotnie kryzysy wywołane przez publikacje dziennikarzy śledczych, w których ujawniali oni fakty niewygodne dla członków Rady Ministrów, związane bezpośrednio z ich nagannymi działaniami lub pośrednio z aktywnością ich najbliższych współpracowników. Celem artykułu jest wykazanie, że demaskowanie przez reporterów dochodzeniowych afer z udziałem członków rządu, ich najbliższych współpracowników lub polityków i urzędników z zaplecza politycznego stanowi swoisty katalizator generujący kryzysy gabinetowe, włącznie z zakończeniem misji Rady Ministrów. Analizie poddano wpływ skandali ujawnionych w czasie misji czterech rządów: W. Pawlaka, L. Millera, J. Kaczyńskiego i D. Tuska.
Śledztwa dziennikarskie a kryzysy gabinetowe w III RP (na wybranych przykładach)
Keywords: cabinet crisis; journalistic investigations; political scandals; kryzys gabinetowy; dziennikarskie śledztwa; afery polityczne